Safety, tolerability, pharmacokinetics, and pharmacodynamics of low dose lysergic acid diethylamide (LSD) in healthy older volunteers - Neiloufar Family; Emeline L. Maillet; Luke T. J. Williams; Erwin Krediet; Robin L. Carhart-Harris; Tim M. Williams; Charles D. Nichols; Daniel J. Goble; Shlomi Raz (Psychopharmacology, 2020)
Abstract Research has shown that psychedelics, such as lysergic acid diethylamide (LSD), have profound anti-inflammatory properties mediated by 5-HT 2A receptor signaling, supporting their evaluation as a therapeutic for neuroinflammation associated with neurodegenerative disease. Objective This study evaluated the safety, tolerability, pharmacokinetics, and pharmacodynamics of orally repeated administration of 5 μg, 10 μg, and 20 μg LSD in older healthy individuals. In the current paper, we present safety, tolerability, pharmacokinetics, and pharmacodynamic measures that relate to safety, tolerability, and dose response. Methods This was a phase 1 double-blind, placebo-controlled, randomized study. Volunteers were randomly assigned to 1 of 4 dose groups (5 μg, 10 μg, 20 μg LSD, and placebo), and received their assigned dose on six occasions (i.e., every 4 days). Results Forty-eight older healthy volunteers (mean age = 62.9 years) received placebo ( n = 12), 5 μg ( n = 12), 10 μg ( n = 12), or 20 μg ( n = 12) LSD. LSD plasma levels were undetectable for the 5 μg group and peak blood plasma levels for the 10 μg and 20 μg groups occurred at 30 min. LSD was well tolerated, and the frequency of adverse events was no higher than for placebo. Assessments of cognition, balance, and proprioception revealed no impairment. Conclusions Our results suggest safety and tolerability of orally administered 5 μg, 10 μg, and 20 μg LSD every fourth day over a 21-day period and support further clinical development of LSD for the treatment and prevention of Alzheimer’s disease (AD).

Safety and efficacy of percutaneous pulsed radiofrequency treatment at the C1–C2 level in chronic cluster headache: a retrospective analysis of 21 cases - Tim Kelderman; Giel Vanschoenbeek; Erwin Crombez; Koen Paemeleire (Acta Neurologica Belgica, 2019)

A robust impact assessment that informs actionable climate change adaptation: future sunburn browning risk in apple - Leanne Webb; Rebecca Darbyshire; Tim Erwin; Ian Goodwin (International Journal of Biometeorology, 2017)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

15 years of processing and dissemination of SPOT-VEGETATION products - Bart Deronde; Walter Debruyn; Eric Gontier; Erwin Goor; Tim Jacobs; Sara Verbeiren; Johan Vereecken (International Journal of Remote Sensing, 2014)

In situ dark field microscopy for on-line monitoring of yeast cultures - Ning Wei; Jia You; Karl Friehs; Erwin Flaschel; Tim Wilhelm Nattkemper (Biotechnology Letters, 2007)